2005
DOI: 10.1562/2005-06-08-ra-568
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Properties of Pro‐multimodal Imaging Agents Derived from a NIR Dye and a Metal Chelator

Abstract: Monomolecular multimodal imaging agents (MOMIAs) are able to provide complementary diagnostic information of a target diseased tissue. We developed a convenient solid-phase approach to construct two pro-MOMIAs (before incorporating radiometal) derived from 1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraacetic acid (DOTA) and cypate, a near-infrared (NIR) fluorescent dye analogous to indocyanine green (ICG). The possible interaction between d orbitals of transition metal DOTA complexes or free metals and the p or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…Using cypate (which is structurally similar to ICG) conjugated to a DOTA chelating moiety, Zhang and Achilefu26 demonstrated that the fluorescent properties can be retained in dual-labeled agents, a finding that is also substantiated by the invivo imaging work described earlier. Similar to the study by Sampath et al,25 Xu et al27 dual-labeled trastuzumab with a red-excitable dye, Cy5.5, as well as with chelating moiety for eventual use in preclinical studies.…”
Section: Molecular Imaging With Near-infrared Fluorescence Imagingmentioning
confidence: 69%
“…Using cypate (which is structurally similar to ICG) conjugated to a DOTA chelating moiety, Zhang and Achilefu26 demonstrated that the fluorescent properties can be retained in dual-labeled agents, a finding that is also substantiated by the invivo imaging work described earlier. Similar to the study by Sampath et al,25 Xu et al27 dual-labeled trastuzumab with a red-excitable dye, Cy5.5, as well as with chelating moiety for eventual use in preclinical studies.…”
Section: Molecular Imaging With Near-infrared Fluorescence Imagingmentioning
confidence: 69%
“…DOTA-Gly-Ser-Gly-Lys(Cypate)-E-Ahx-NH2,LS444, was synthesized and radiolabeled with 111 InCl 3 (MSD-Nordion, Kanata, ON, Canada, 3.0 microcuries (µCi)) in aqueous buffer (190µl, 0.4 M sodium acetate, pH 4.5, 30 min, 98 °C) as described previously (6, 7). Labeling efficiency and radiochemical purity were checked by HPLC (Supelcosil ABZ + PLUS, HPLC Column, 15cm X 4mm, 5µm) with a gradient of H 2 O and acetonitrile containing 0.1% TFA.…”
Section: Methodsmentioning
confidence: 99%
“…Alternatively mutliple molecular contrasts might be joined through specific links (4–6). For example optical methods have unique activation contrast mechanisms, which are complementary to PET/SPECT information and the information available to both nuclear and optical contrasts can be harnessed directly using monomolecular optical multimodality imaging agent’s (MOMIA) (4–7). Imaging of MOMIA agents requires suitable instrumentation and algorithms.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The findings should build upon the existing knowledge and make significant strides towards validating multimodal imaging platforms for clinical use. Innovative chemistry strategies to combine chelators and NIRF dyes into a single “reactive” unit have been shown and offer great promise to simplify agent synthesis and broaden the use of multimodal probes [6770]. Given the importance of mAb-based targeting approaches, such platforms may help mitigate the loss of immunoreactivity that can occur following multistep conjugations at random sites on mAbs or mAb fragments.…”
Section: Future Directionsmentioning
confidence: 99%